Conscientiousness and Cardiometabolic Risk: A Test of the Health Behavior Model of Personality Using Structural Equation Modeling. Issue 1 (19th April 2021) - Thomas, Mark C; Duggan, Katherine A; Kamarck, Thomas W; Wright, Aidan G C; Muldoon, Matthew F; Manuck, Stephen B
Abstract: Background: High trait conscientiousness is associated with lower cardiometabolic risk, and health behaviors are a putative but relatively untested pathway that may explain this association. Purpose: To explore the role of key health behaviors (diet, physical activity, substance use, and sleep) as links between conscientiousness and cardiometabolic risk. Methods: In a cross-sectional analysis of 494 healthy, middle-aged working adults (mean age = 42.7 years, 52.6% women, 81.0% White), participants provided self-reports of conscientiousness, physical activity, substance use, diet, and sleep, and wore monitors over a 7-day monitoring period to assess sleep (Actiwatch-16) and physical activity (SenseWear Pro3). Cardiometabolic risk was expressed as a second-order latent variable from a confirmatory factor analysis involving insulin resistance, dyslipidemia, obesity, and blood pressure. Direct, indirect, and specific indirect effect pathways linking conscientiousness to health behaviors and cardiometabolic risk were examined. Unstandardized indirect effects for each health behavior class were computed separately using bootstrapped samples. Results: After controlling for demographics (sex, age, race, and education), conscientiousness showed the predicted, inverse association with cardiometabolic risk. Among the examined health behaviors, objectively-assessed sleep midpoint variability ( b = −0.003, p = .04), subjective sleep quality ( b = −0.003, p = .025), and objectively-assessed physical activity ( b = −0.11, p = .04) linked conscientiousness to cardiometabolic risk. Conclusions: Physical activity and sleep partially accounted for the relationship between conscientiousness and cardiometabolic risk. Abstract : Favorable physical activity and sleep habits during daily life may explain how conscientious personality traits are linked with metabolic and heart health.